(untitled) (Global Journal of Management and Business Research, 2019)
This paper examines Senior Citizens#x2019; intention towards using digital banking in a context where there is a rapid development in online banking systems in Sri Lanka. It was revealed that most of the Senior Citizens are away from the digital banking platform even though bank has made huge investments for the implementation of the digital banking systems. Therefore, the aim of this research is to investigate the impact of perceived usefulness and perceived ease of use, on the behavioral intention of Senior Citizen to use the digital banking system with the application of Technology Acceptance Model (TAM). The structured questionnaire used as the main instrument in gathering primary data from 200 respondents from 20 branches of the selected commercial banks using convining sampling method. This study investigated that there is a positive relationship between perceived usefulness and beheviroal intention, also between perceived ease of use and beheviroal intention.